The Politics of Interstices: «De Liberalitate et Parismonia» in Nicholas Macchiavello’s The Prince - Gaune, Rafael (2019)
This article proposes an annotated review of «De liberalitate et parsimonia», chapter XVI of Nicholas Macchiavello’s The Prince. It addresses how the Florentine author exposes the exceptionalities of misery and liberality as a mechanism of adaptation and interpretation of political reality. Both misery and liberality are part of a schema that expresses the nuances, exceptions, and twilights of real politics as well as the limits of human virtues.Also, this article dialogues with other Macchiavello’s texts (letters and Discorsi) and other chapters of The Prince.